Wage differential between Palestinian non-refugees and Palestinian refugees in the West Bank and Gaza - Sameh Hallaq (Levy Economics Institute of Bard College, 2019)
This paper measures the wage differential between Palestinian non-refugees and Palestinian refugees in the West Bank and Gaza over the years 1999-2012. First, the main individual and occupational differences between the two groups in the two regions are presented. Then, the wage differential is decomposed into two components: a "human capital effect, explained part" and a "coefficient effect, unexplained part." Second, findings suggest that though the wage gap has always existed and favored non-refugees in the West Bank, it has a more substantial impact among low-skilled workers and those in the private sector. Furthermore, most of this gap is attributed to the unexplained part of the wage decomposition model. In Gaza, the wage gap favored refugee workers. Most of this wage gap among unskilled workers is attributed to the endowment/human capital effect, while for skilled workers most of the wage gap is due to the unexplained part - the "coefficient effect" - after 2006.
Keywords: J31; J71; 330; West Bank; Gaza Strip; Wage Differential; Refugees